DNA-dependent PK inhibits adeno-associated virus DNA integration - Song, Sihong (National Academy of Sciences, 2004)
Recent studies have shown that recombinant adeno-associated virus (rAAV) can persist in episomal form; however, factors affecting rAAV persistence are poorly understood. DNA-dependent PK (DNA-PK) is a DNA repair enzyme, which we previously found played an important role in determining the molecular fate of the rAAV genome in mouse skeletal muscle. In the present study, we tested the effect of DNA-PK on AAV serotype 2 integration in vitro and in vivo in mouse liver. In an in vitro integration system, addition of DNA-PK decreased AAV integration, whereas antibody against DNA-PKcs increased integration. In vivo, matched doses of a recombinant AAV serotype 2 vector were injected into the portal vein of either C57BL/6 (DNA-PKcs(+/+)) or severe combined immunodeficient (DNA-PKcs(-/-)) mice. After partial hepatectomy to stimulate hepatocyte proliferation, retention of vector genomes and of transgene expression was substantially higher in severe combined immunodeficient mice, indicating that in the absence of DNA-PKcs, a greater proportion of genomes integrated into the cellular genome. In summary, we have provided evidence that DNA-PK inhibits AAV integration both in vitro and in vivo.